Research on climate change adaptation in the Program for Climate-Smart Livestock - Crane, Todd A. (International Livestock Research Institute, 2020)
The Program for Climate-Smart Livestock (PCSL) looks at innovative practices in livestock systems, in relation to their mitigation and adaptation potential. The social dimensions as well as bio-physical dimensions of these practices will be analysed. Adaptation tracking tools will also be developed.